Intestinal Microbiome Richness of Coral Reef Damselfishes (Actinopterygii: Pomacentridae). Issue 1 (16th September 2022) - Kavazos, Christopher R J; Ricci, Francesco; Leggat, William; Casey, Jordan M; Choat, J Howard; Ainsworth, Tracy D
Abstract: Fish gastro-intestinal system harbors diverse microbiomes that affect the host's digestion, nutrition, and immunity. Despite the great taxonomic diversity of fish, little is understood about fish microbiome and the factors that determine its structure and composition. Damselfish are important coral reef species that play pivotal roles in determining algae and coral population structures of reefs. Broadly, damselfish belong to either of two trophic guilds based on whether they are planktivorous or algae-farming. In this study, we used 16S rRNA gene sequencing to investigate the intestinal microbiome of 5 planktivorous and 5 algae-farming damselfish species ( Pomacentridae ) from the Great Barrier Reef. We detected Gammaproteobacteria ASVs belonging to the genus Actinobacillus in 80% of sampled individuals across the 2 trophic guilds, thus, bacteria in this genus can be considered possible core members of pomacentrid microbiomes. Algae-farming damselfish had greater bacterial alpha-diversity, a more diverse core microbiome and shared 35 ± 22 ASVs, whereas planktivorous species shared 7 ± 3 ASVs. Our data also highlight differences in microbiomes associated with both trophic guilds. For instance, algae-farming damselfish were enriched in Pasteurellaceae, whilst planktivorous damselfish in Vibrionaceae . Finally, we show shifts in bacterial community composition along the intestines. ASVs associated with the classes Bacteroidia, Clostridia, and Mollicutes bacteria were predominant in the anterior intestinal regions while Gammaproteobacteria abundance was higher in the stomach. Our results suggest that the richness of the intestinal bacterial communities of damselfish reflects host species diet and trophic guild.